Perayaan 1 Muharram: Sejarah, Tradisi, Dan Makna Dalam Konteks Islam - Muhammad Farchani; Daud Rismana; Helmi Haidar Nabil; Aysyah Ratna Ningrat; Putri Nuril Hitkayati; Ade Ulfal Alfiatun Ni'mah; Septian Hidayatul Aulia; Andre Novianto (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This article discusses the celebration of 1 Muharram, which marks the Hijri New Year in the Islamic calendar. In celebrating or commemorating the Islamic New Year 1446 Hijri, some people commemorate it with various activities such as a torch parade around the village. In Wates village, there are many traditions and customs in commemorating this special day. The purpose of this celebration is a spiritual form that is still attached to the local community. This research covers the history of the beginning of the celebration, traditions that developed in various parts of the world to those that developed in Indonesia, especially in Wates Village, Batang, as well as the spiritual and social meaning of the day for Muslims. The research method includes literature study and qualitative data analysis from primary and secondary sources. From this explanation, it can be seen how attached the tradition and culture in the local community will be to the presence of the Islamic New Year.